Teknik Komunikasi Persuasif Pimpinan Pondok Pesantren Darul Arafah Raya dalam Mengoptimalkan Citra Positif di Kalangan Masyarakat Sumatera Utara - Siti Zahara; Efi Brata Madya (Journal of Education on Social Science (JESS), 2023)
This study aims to determine how the persuasive communication techniques of Darul Arafah Islamic boarding school in optimizing a positive image among the people of North Sumatra. This research uses descriptive qualitative techniques using data collection methods by means of semistructured interviews, observation and documentation. Data analysis using analysis techniques with four processes, namely data collection, data reduction, data dispalay and data verification. Then tested the validity of the data using data validity techniques in the form of tringulation of sources, techniques and time. The results of the research on persuasive communication techniques on the part of the Darularafah Islamic boarding school introduce this pesantren by inviting and determining marketing strategies in attracting public interest, namely with activities that are useful and in accordance with the needs of the local community such as holding bazaars, etc. and the pesantren also conducts social activities such as, gotong royong, mass circumcision, recitation, celebrating the independence day of the Indonesian republic, celebrating Islamic days (isrami'raj, one muharram, etc.) to attract the public by uploading positive content by spreading information that darularafah does not teach religious knowledge only but general knowledge as well. So that its alumni can continue their studies to general universities (USU, UI, UGM, IPB, UNIMED, UNPAD, etc.) of course to religious universities (IAIN Indonesia, Al Azhar / Egypt, Univ. Madinah/Saudi Arabia